INTERACTIVE LEARNING MEDIA DESIGN MARITIME ENGLISH - Vega Andromeda Fonsula (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
This research was conducted to design an English learning media with the aim of developing the cadets' cognitive abilities in pronunciation and memorization of maritime English. So that this interactive learning media fosters elaboration in learning because it is accompanied by graphic and audio elements. This study uses a Design and development research (DDR) approach. Richey & Klein 2014 a systematic study of the design, development, and assessment process with the aim of providing an empirical basis for the production of instructional and non-instructional goods and tools, as well as new or improved development models. Design includes analysis, design and coding with animation maker software. The design of interactive learning media includes storyboard designs, environment designs for maritime learning and menu designs. The design of the storyboard contains the storyline of the interactive learning media delivered using animated images and audio. In this interactive media, there are several options and level facilities. Meanwhile, the environmental design is the background of the illustration focusing on the case method of learning English in maritime. The menu design describes learning interactions with the Things Around Us, Part of Maritime, Environment, Quiz, and Back to the previous menu facilities. At a deeper level in the “Things around us” facility, there are interactive learning activities such as work safety, environmental maritime, maritime activity. The Quiz option facility is used to test the cadets' ability to learn interactive media outcomes. The design of this learning media and the sound effects available when answering it, can improve the pronunciation and understanding of English for the cadets.